Effects of extraction conditions on antioxidant properties of sapodilla fruit (Manilkara zapota) - Woo, F. P.; Yim, Hip Seng; Khoo, Hock Eng; Sia, Chiaw Mei; Ang, Yee Kwang (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
This study investigated the effects of different percentages of ethanol (0 - 100%), extraction times (1 - 5 h) and temperatures (25 - 60°C) on total phenolic content (TPC) and antioxidant activity (AA) of sapodilla pulp and peel. TPC was determined by Folin-Ciocalteu reagent method, while AA was evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, 2,2-azino-bis-(3-ethyl-benzothiazoline-6-sulfonic acid) (ABTS) radical scavenging assay, ferric reducing antioxidant power (FRAP) assay and ß-carotene bleaching (BCB) assay. Based on the optimal extraction conditions used, sapodilla pulp extract had TPC of 3.89 mg GAE/g, 63.20% of DPPH scavenging activity, 4.30% of ABTS scavenging activity, 19.17% of BCB activity, and FRAP value of 15.24 mg TE/g; while its peel extract had TPC of 9.23 mg GAE/g, 92.95% of DPPH scavenging activity, 5.36% of ABTS scavenging activity, 8.14% of BCB activity, and 27.85 mg TE/g (FRAP value). Using the optimal extraction conditions for sapodilla pulp (40% ethanol as extraction solvent that extracted at 60°C for 4 h) and sapodilla peel (80% ethanol and 2 h extraction time at 40°C), highest antioxidants can be extracted from the pulp and peel.